Factor that influences customers’ perception towards Islamic banking facilities / Muhammad Shahrul Zawawi Kamaruddin and Muhamad Hafizuddin Ja’apar - Kamaruddin, Muhammad Shahrul Zawawi; Ja’apar, Muhamad Hafizuddin (Faculty of Business and Management, 2014)
The purpose of this study is to analyse Factor that influences customers‟ perception towards Islamic banking facilities. For this study only 100 of respondents which are employees of Johor Land Berhad and Johor Silica Industries Sdn. Bhd were selected and act as respondent for this study. The objectives of this study are to examine if the factor of banks image and reputation, quality services and religiosity can influence customers‟ perception towards Islamic banking facilities. Other than that, this study also will identify which is most influence factor that contributed to the customers towards Islamic banking facilities. Besides that, this study is a quantitative research study whereby the findings of the study were analysed by using the Statistical Package for the Social Sciences (SPSS). Next, the data collected in this study is analyses by using frequency, descriptive analysis, reliability test, and Pearson correlation coefficient.